Students Critical Thinking Skills in Physical Education Learning: A Systematic Literature Review - Septian, Regi Dwi; Al Ghazaly, Muhammad Dzikry Abdullah; Riansyah, Riansyah Riansyah; Majeed, Hasmiza Abdul (Journal of Physical Education For Secondary Schools, 2023)
This research was conducted to determine the level of students' critical thinking skills regarding physical education learning. Research shows that students' critical thinking skills are very good. Where students in cognitive organizing focus on problem solving. The research method used is Systematic Literature Review (SLR) using the Publish or Perish application and the Google Scholar site. This research protocol uses PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Of the 135 relevant articles, classification was carried out and 8 classifications (31 articles) were selected which were selected as "critical thinking" according to the topic of discussion, with 16 articles. At the included stage, by carrying out inclusion and exclusion, 2 relevant articles were obtained. The results obtained are that by being taught critical thinking skills, students are empowered to analyze, evaluate and make the right decisions about the world around them. Teachers design learning by providing problems that involve students' thinking skills and include analytical processes based on real problems.